Physical Modeling of the Stability of a Revetment Breakwater Built on Reclaimed Coral Calcareous Sand Foundation in the South China Sea—Regular Wave - Kunpeng He (Applied Sciences, 2021)
In the past several years, a series of artificial islands have been constructed on the top of coral reefs by China in the South China Sea by way of reclamation. A large number of revetment breakwater also has been built along the margin of these artificial islands. The stability of these revetment breakwater is the precondition for the normal service performance of these reclaimed coral sand islands. In this study, taking the reclamation engineering in the South China Sea as the background, a series of wave flume physical model tests (geometrical similarity scale is set to 1:10) are performed to investigate the dynamics and the stability of the revetment breakwater and its reclaimed coral sand foundation under the impact of regular wave. Experimental results show that the revetment breakwater has a maximum final settlement of 6 mm if built on loose coral sand foundation. Furthermore, there is indeed excess pore pressure generated in the reclaimed coral foundation with a maximum magnitude of 1.5 kPa. It is found that the excess pore pressure has not caused liquefaction in the coral sand foundation due to the fact that the accumulation of excess pore pressure only occurred in the first 10 cycles of wave loading. Finally, it is concluded that the revetment breakwater and its reclaimed coral sand foundation basically are stable under regular wave impacting. However, excessive water overtopping would be a potential threat for the vegetation behind the breakwater, as well as for the desalinated underground water of the reclaimed lands.